The Development of Methods for the Innovation Infrastructure Progress in Crimea Region - NALIVAYCHENKO, Ekaterina; KIRILCHUK, Svetlana (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
This article deals with study of the role of innovation infrastructure in the regional innovation system stems from the fact that currently the scientific community much attention is paid to the study of regional innovative systems, but not so many works that addressed issues of providing conditions for the development of these systems. We believe that the most important of these conditions is the formation in the regions of well-functioning innovation infrastructure. In this regard, of particular scientific interest is the study of the place and role of innovation infrastructure in the regional innovation system. Identifying the role of innovation infrastructure in the innovation system requires the definition of ‘innovation system’. The concept of innovation systems appeared relatively recently and is the epitome of a widely used systematic approach to the study of innovation. This approach allows us to consider innovative development from the point of view of system of interactions between its participants since the inception of innovations and their implementation. In this article we demonstrate the need for transformation of internal and international profile of Crimea: progressive development of high-technology products and services. In addition, we evaluate prospects for state commercialization of scientific results. A solution to a problem of Crimea innovation infrastructure development can provide steady social and economic development of Russian economy within innovations. Implementation of innovation regional infrastructure policy would present local enterprises with landmarks for development of long-term projects, exploration of new local and foreign market niches within the ‘knowledge-based economy’. At that, there are several more important components of regional strategy for development of innovation infrastructure: progressive transformation of type of international specialization, export diversification, expansion of market share of home high-technology products and services.